2018
DOI: 10.1002/jcb.27425
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose nonfermenting AMPK‐related kinase (SNARK) regulates exercise‐stimulated and ischemia‐stimulated glucose transport in the heart

Abstract: The signaling mechanisms mediating myocardial glucose transport are not fully understood. Sucrose nonfermenting AMP-activated protein kinase (AMPK)-related kinase (SNARK) is an AMPK-related protein kinase that is expressed in the heart and has been implicated in contraction-stimulated glucose transport in mouse skeletal muscle. We first determined if SNARK is phosphorylated on Thr , a site critical for SNARK activity. Mice were treated with exercise, ischemia, submaximal insulin, or maximal insulin. Treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Finally, RNA seq analysis of the liver revealed that treatment with HMH2 induced a 1.29-fold increase (0.37 log2 fold change) in Nuak2 transcript expression versus the HFHS diet control. Nuak2, also termed SNARK, has been identified as a mediator of insulin-independent glucose transport, specifically regulating exercise-and ischemia-stimulated glucose transport in the heart and contraction-stimulated glucose transport in skeletal muscle [56,57]. However, our understanding of SNARK's impact on glucose metabolism is still quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, RNA seq analysis of the liver revealed that treatment with HMH2 induced a 1.29-fold increase (0.37 log2 fold change) in Nuak2 transcript expression versus the HFHS diet control. Nuak2, also termed SNARK, has been identified as a mediator of insulin-independent glucose transport, specifically regulating exercise-and ischemia-stimulated glucose transport in the heart and contraction-stimulated glucose transport in skeletal muscle [56,57]. However, our understanding of SNARK's impact on glucose metabolism is still quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glucose uptake induced by exercise was abolished in heterozygous SNARK knockout mice. In HL1 cardiomyocytes, knockdown of SNARK resulted in a decreased glucose uptake and ischemia-induced phosphorylation of TBC1D4 at Ser711, while insulin-stimulated TBC1D4 phosphorylation was unaffected [70]. Collectively, the data suggest that SNARK may act in a pathway downstream of LKB1 to influence exercise-induced glucose uptake in skeletal muscle and the heart, presumably via phosphorylation of the RabGAPs.…”
Section: Snark and Ark5 Present Promising Upstream Kinases Of Tbc1d1 ...mentioning
confidence: 78%
“…Overexpression of mtSNARK and heterozygous SNARK whole-body knockout also led to reduced TBC1D4 and TBC1D1 phosphorylation induced by contraction (as determined using PAS antibody). Furthermore, heterozygous SNARK depletion reduced glucose uptake induced by in vitro contraction in soleus muscle and induced by treadmill exercise in gastrocnemius muscle [67,70]. Insulin-stimulated glucose uptake, however, remained unaltered by the overexpression of mtSNARK or heterozygous SNARK knockout [67].…”
Section: Snark and Ark5 Present Promising Upstream Kinases Of Tbc1d1 ...mentioning
confidence: 95%
See 1 more Smart Citation